The prevalence of Anopheles (Diptera: Culicidae) mosquitoes in Sekong Province, Lao PDR in relation to malaria transmission - Vythilingam, Indra; Phetsouvanh, R.; Keokenchanh, K.; Yengmala, V.; Vanisaveth, V.; Phompida, S.; Hakim, S.L. (Wiley, 2003)
A longitudinal study was conducted on the prevalence of Anopheles in three malaria endemic villages in Sekong province, in the southern region of Lao PDR, from August 2000 to October 2001. All night, human landing collections took place in August and October 2000 and April and October 2001, and blood smears were taken for malaria parasites during the same period. Mosquitoes were tested for sporozoite antigen using enzyme-linked immunosorbent assay. In August 2000 (wet season) and April 2001 (dry season) the ovaries of the mosquitoes were examined for parity. A total of 16 species of Anopheles were caught in the study sites of which An. dirus A, An. maculatus sl and An. jeyporiensis were positive for sporozoites. The entomological inoculation rate (EIR) ranged from 0.06 to 0.25. There was a good correlation between EIR and vectorial capacity in the wet season, especially in Pai Mai where the prevalence of malaria was also high during the wet seasons (11.8 and 10.53). An. dirus A showed ambivalence in their choice of feeding as approximately 50 attacked man indoors and an equal proportion outdoors. An dirus A was the main vector in Pai Mai. The parous rate did not significantly differ between the wet and dry season, although it was higher in the dry season. In Takaio the parasite prevalence ranged from 8.7 (dry season) to 37.1 (wet season) and An. jeyporiensis was the vector, and the risk of infection was 0.85 in the dry season while 0.99 in the wet season. In Toumgno An. maculatus sl was the vector and infection was found only in August and October 2000. However, malaria prevalence ranged from 9.69 to 20.4 and was equally high in the dry season. Cattle were also present close to the houses in all the villages and this might be a contributory factor in the prevalence of malaria.